Legacy of the "Perestroika" Policy in Karakalpakstan (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
The article illuminates the history of Karakalpakstan at a pivotal moment: when national leaders took office after the tragic events of the "cotton business." Based on the latest literature and archival sources, the author reconstructs these dramatic pages of our people.